Hydrogen production by steam methane reforming in a membrane reactor equipped with a Pd composite membrane deposited on a porous stainless steel. (12th April 2018) - Kim, Chang-Hyun; Han, Jae-Yun; Kim, Sehwa; Lee, Boreum; Lim, Hankwon; Lee, Kwan-Young; Ryi, Shin-Kun
Abstract: With the aim of producing hydrogen at low cost and with a high conversion efficiency, steam methane reforming (SMR) was carried out under moderate operating conditions in a Pd-based composite membrane reactor packed with a commercial Ru/Al2 O3 catalyst. A Pd-based composite membrane with a thickness of 4–5 μm was prepared on a tubular stainless steel support (diameter of 12.7 mm, length of 450 mm) using electroless plating (ELP). The Pd-based composite membrane had a hydrogen permeance of 2.4 × 10 −3 mol m −1 s −1 Pa −0.5 and an H2 /N2 selectivity of 618 at a temperature of 823 K and a pressure difference of 10.1 kPa. The SMR test was conducted at 823 K with a steam-to-carbon ratio of 3.0 and gas hourly space velocity of 1000 h −1 ; increasing the pressure difference resulted in enhanced methane conversion, which reached 82% at a pressure difference of 912 kPa. To propose a guideline for membrane design, a process simulation was conducted for conversion enhancement as a function of pressure difference using Aspen HYSYS ® . A stability test for SMR was conducted for ∼120 h; the methane conversion, hydrogen production rate, and gas composition were monitored. During the SMR test, the carbon monoxide concentration in the total reformed stream was <1%, indicating that a series of water gas shift reactors was not needed in our membrane reactor system. Graphical abstract: Highlights: CH4 conversion reached ∼82% at a ΔP = 912 kPa at 823 K in Pd/PSS membrane reformer. H2 ∼97.7% was obtained in the permeate stream with CO2 60% in the retentate stream. MSR results in Pd/PSS membrane reactor was well agreement with simulation results.